Усовершенствование методологии расчета распределенной системы тягового электроснабжения с усиливающим пунктом - Сыченко, Виктор Григорьевич; Босый, Дмитрий Алексеевич; Косарев, Евгений Николаевич (НТУ "ХПИ", 2014)
В статье проанализированы основные способы усиления тяговой сети постоянного тока. На примере реального участка выполнены оценочные расчеты обеспечения уровня напряжения при установке усиливающего пункта в середине межподстанционной зоны узловой схемы питания. Предложен аналитический способ расчета тока усиливающего пункта, применимый для реальных реализаций тяговых токов в условиях эксплуатации.

The existing methods of enhancing the centralized DC traction power supply systems don’t provide a sufficient level of the voltage at the different operating conditions. Alternatively the distributed power supply system with using autonomous enhancing points on electrified line may provide the required voltage mode. The distributed power supply system also allow to regulate the voltage in the fixed range. The methodology used in this work shows that the voltage in the traction network may be regulated by a certain value of the current and the quantity of the enhancing points. The results that obtained in this work provide the methodological basis for the distributed power system of the DC traction network with enhancing points and allow to control the each of them in a real time in a common system of intellectual power supply.
The methodology improvement for calculating the distribution traction power supply system with enhanced point
Keywords: постоянный ток; уровень напряжения; усиление тяговой сети; узловая схема питания; power supply; traction; direct current; voltage level; enhancing; distributed system